Análise da relação entre perfil psicológico e performance de day traders no mercado futuro da B3 - Paulo Celso Pires Sant'Ana (2020)
Decision making is not always based on rationality. A number of behavioral / emotional changes can be responsible for changing the performance of a financial market agent. Thus, this research aimed to analyze the profile of day traders operating in the B3 futures market, with a view to assessing the relationship between factors and personality traits in the performance of these traders, as well as identifying the existence of the disposition effect and its relationship with financial results, by means of data from the negotiation of futures contracts on a daily basis. The factors are: Neuroticism, Extroversion, Openness, Agreeableness and Conscientiousness. There are six traits for each of these factors. It was a descriptive study with a qualitative and quantitative approach. Data collection took place through the NEO PIR Personality Inventory and the performance report of 53day traders. The results were analyzed using descriptive statistics on the sociodemographic conditions of the sample; of pseudo median tests; verifying the existence of the disposition effect; factor analysis to understand which personality traits are most relevant to each of the five factors; and the logistic regression that verified the relationship between the personality domains, arising from the Big Five Theory, and its relationship with the performance of the day traders working at B3. The main results were: In the descriptive statistics, day traders with “very high” Neuroticism obtained an average net loss of R$ 6,533.17, while those classified with “very low” Neuroticism obtained an average net profit of R$ 21,856, 90. Regarding the Extroversion domain, those that were classified in the “Very High” range, were on average profitable at R $ 18,064.60, while those in the “Very Low” range obtained, on average, a loss of R$ 12,770.46; through the test of differences in means, it was identified that the domains Neuroticism and Extroversion have a statistically significant difference in relation to the classifications of satisfactory and unsatisfactory performance. Regarding the perception of personality, the most important traits were: depression, gregariousness, aesthetics, complacency and competence. In the identification of emotional and / or behavioral aspects that affect the probability of day traders reaching a profitable performance, the Conscientiousness factor was the statistically relevant; the most important personality traits were: depression, complacency and competence. Regarding the disposition effect, one can conclude its prevalence among day traders who obtained an unsatisfactory performance, among women and among older traders. These day traders had a loss (net financial result) at the end of the three months of daily trading. This result can be explained by the delay in leaving losing operations at the expense of the short stay in winning operations. In other words, in a situation of imminent loss, these day traders took more risk than in imminent gain operations. In addition, People with "high" and "very high" Consciousness do not usually suffer from disposition effect.